2005
DOI: 10.1097/01.jnen.0000183345.19447.8e
|View full text |Cite
|
Sign up to set email alerts
|

Altered Expression of Immune Defense Genes in Pilocytic Astrocytomas

Abstract: Pilocytic astrocytoma (WHO grade I) is a circumscribed, slowly growing, benign astrocytoma that most frequently develops in the cerebellar hemispheres and in midline structures and occurs predominantly in childhood and adolescence. In contrast to diffusely infiltrating gliomas in adults (e.g. grade II astrocytomas, oligodendrogliomas), survival of patients with pilocytic astrocytoma is excellent after surgical intervention. To search for potential molecular mechanisms underlying its benign biologic behavior, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 28 publications
5
44
0
3
Order By: Relevance
“…In contrast to primary glioblastomas, 34 EGFR is absent or very low in pilocytic astrocytomas. 35 Thus, in pilocytic astrocytomas, the increased expression levels of annexin-1 do not parallel with higher EGFR levels, indicating an additional function of annexin-1 besides serving as a substrate for EGFR.…”
Section: Annexin-1 In Neuroepithelial Tumorsmentioning
confidence: 99%
“…In contrast to primary glioblastomas, 34 EGFR is absent or very low in pilocytic astrocytomas. 35 Thus, in pilocytic astrocytomas, the increased expression levels of annexin-1 do not parallel with higher EGFR levels, indicating an additional function of annexin-1 besides serving as a substrate for EGFR.…”
Section: Annexin-1 In Neuroepithelial Tumorsmentioning
confidence: 99%
“…PA is a circumscribed, slow-growing, benign astrocytoma that occurs predominantly in childhood and adolescence (14). Despite an extensive literature search, only one report of a PA associated with pregnancy exists and it had required tumor resection (6).…”
Section: Discussionmentioning
confidence: 99%
“…It occurs predominantly in childhood and adolescence (14). Growth of PA during pregnancy is rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…These observations could be a result of interactions with pro-MMP-9 and the angiogenesispromoting ability of this MMP. Huang et al (2005) and Pagentecher et al (1999) found higher levels of TIMP-1 expression in pilocytic astrocytomas and glioblastomas. This result seems contradictory, but it may act to offset the simultaneous increases in the expression of MMP-9 and TIMP-1 because TIMP-1 preferentially inhibits MMP-9.…”
Section: The Role Of Timps In the Progression Of Astrocytic Tumorsmentioning
confidence: 99%
“…TIMP-2 preferentially inhibits MMP-2 and activates pro-MMP-2 by forming complexes with MT1-MMP. Béliveau et al (1999), Huang et al (2005) and Nakada et al (2001) suggests that there is an inverse correlation between the expression of TIMP-2 and the degree of malignancy in CNS tumors. This result may be related to the antagonistic effects of these genes in the classical biological behavior of astrocytic tumors, in which MMPs act as promoters of invasion and TIMPs as blockers of tumor growth.…”
Section: The Role Of Timps In the Progression Of Astrocytic Tumorsmentioning
confidence: 99%